Фінансовий ризик при формуванні стратегії сталого розвитку підприємства - Березянко, Тамара Володимирівна; Костриця, Олександра Валентинівна; Дорошенко, Владислав Олександрович (My University, 2022)
Стаття присвячена теоретичним та практичним аспектам з формуванню програми сталого розвитку при наявності фінансових ризиків на підприємстві. Проаналізовані різні поняття науковців, щодо таких термінів: «ризик», «фінансовий ризик» та «сталий розвиток підприємства». Розглянуто основні складові сталого розвитку підприємства та вплив на нього фінансового ризику. Проаналізовано ринок продуктів сухих сніданків в Україні та рівень фінансового стану досліджуваного підприємства ПрАТ «Лантманнен Акса», Проаналізовано вплив всіх фінансових показників та наявність фінансових ризиків. Запропоновано заходи щодо зниження фінансових ризиків, створено нова програма сталого розвитку ПрАТ «Лантманнен Акса». The article is devoted to theoretical and practical aspects of forming a ustainable development program in the presence of financial risks in the enterprise. Different сoncepts of scientists regarding the following terms are analyzed: "risk", "financial risk" and "sustainable development of the enterprise". The relevance of the implementation of sustainable development programs by enterprises is determined and the implementation of sustainable development programs at enterprises allows to obtain additional advantages in management and to react quickly to changes in the internal and external environment of the enterprise. The indicators of the economic, social and environmental spheres of the enterprise are considered, which allow us to assess the state of the оrganization in terms of sustainability, and the calculation of the indicators indicated in the article allows us to find the disproportions in the management of sustainable development of the enterprise and to see in which spheres, economic, social or ecological, is more active work to achieve sustainability.The main components of sustainable development of the enterprise and the impact of financial risk on it are considered. The market of breakfast cereals in Ukraine is analyzed, it can be stated that today the market is at a fairly high level of demand, which allows the company to operate successfully and the level of financial condition of the researched enterprise PJSC "Lantmann Aksa". looking at the limitations through COVID-19. It is determined that to develop a strategy to improve sustainable development, you must first assess the financial condition of the enterprise, using SWOT-analysis, calculation of financial performance, for which the following analyzes were developed: horizontal, vertical, comparative and financial ratios, profitability and level bankruptcy. The impact of all financial indicators and the presence of financial risks are analyzed, it is the sustainable development program that directly depends on these indicators, they help to accumulate free funds for its development, so the concepts of financial development and sustainable development are directly proportional. Measures to reduce financial risks have been proposed, and a new program for the sustainable development of PJSC Lantmann Aksa has been created, which allows bringing the company to a new level.
Keywords: сталий розвиток; підприємство; фінансовий стан; ризик; показник; коефіцієнт; рентабельність; ринок; sustainable development; enterprise; financial condition; risk; indicator; coefficient; profitability; market; кафедра економіки праці та менеджменту